Enhancing Students' Mathematical Representation Ability Through the Concrete-Representational-Abstract Approach Integrated to Sirquid Game - Shanti Nurhidayah; Gunawan; Salsabila Anindiyah; Yudistira Indra Prahasta Putra; Setiyani Setiyani; Rahmad Khodari (Universitas Sriwijaya in collaboration with Indonesian Mathematical Society (IndoMS), 2026)
Many elementary school students struggle to represent fractions verbally, visually, and symbolically, which hinders their understanding of fractions in meaningful real-life contexts. This study aimed to examine the effectiveness of the Concrete-Representational-Abstract (CRA) approach integrated with the Sirquid Game in enhancing students’ mathematical representation ability in fractions topics. The study employed a mixed-method approach with an explanatory sequential design. The quantitative phase involved 48 students divided into an experimental group (n = 24) and a control group (n = 24). Data were collected using pretest and posttest instruments measuring verbal, visual, and symbolic representations. Quantitative data were analyzed using non-parametric statistical tests (Wilcoxon Signed-Rank Test and the Mann–Whitney U Test) and N-Gain analysis. The qualitative phase involved semi-structured interviews with three students from the experimental group representing high, medium, and low achievement levels to explore learning experiences and representation processes. The results indicated that students in the experimental group showed a statistically significant improvement compared to the control group (p < 0.05), with a high N-Gain score (0.77). Qualitative findings supported these results by demonstrating that the CRA stages implemented through the Sirquid Game facilitated students’ understanding and use of multiple representations of fractions. These findings suggest that the integration of the CRA approach and game-based learning is effective in enhancing students’ mathematical representation abilities. This study contributes to the development of mathematics teaching strategies, especially for fractions, by integrating step-by-step learning and physical activities, offering an innovative alternative to enhance student engagement and comprehension in elementary education.